Persistent Cutibacterium (Formerly Propionibacterium) acnes Bacteremia and Refractory Endocarditis in a Patient with Retained Implantable Pacemaker Leads. (26th July 2020) - Freedman, M.; Aflatooni, J. O.; Foster, R.; Haggerty, P. G.; Derber, C. J.
Abstract : Cutibacterium (formerly Propionibacterium ) acnes ( C. acnes ) is a commensal bacteria commonly found on the human skin and in the mouth. While the virulence of C. acnes is low in humans, it does produce a biofilm and has been identified as an etiologic agent in a growing number of implant-associated infections. C. acnes infections can prove diagnostically challenging as laboratory cultures can often take greater than 5 days to yield positive results, which are then often disregarded as contaminant. Patients with recurrent bacteremia in the setting of implantable devices warrant further studies to evaluate for an associated valvular or lead endocarditis. The patient in this report demonstrates how cardiac device-related endocarditis secondary to C. acnes can be overlooked due to the indolent nature of this pathogen. This patient presented with an implanted cardiac pacemaker device, as well as retained leads from a prior pacemaker. Transesophageal echocardiography was required to confirm the diagnosis in the setting of multiple positive blood cultures and negative transthoracic echocardiograms over a period of 4 years. The purpose of this report is to highlight the difficulties encountered in diagnosing C. acnes endocarditis in a patient with a cardiac implantable electronic device and persistently positive blood cultures.